2017
DOI: 10.1002/jum.14219
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Hepatic Toxicity in Rats Induced by Inhalable Silica Nanoparticles Using Acoustic Radiation Force Imaging

Abstract: Inhalable SiO nanoparticles and SiO /PPE were able to induce hepatic injury in rats. Using ARFI to evaluate hepatic toxicity induced by SiO nanoparticles was effective in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among them, the adsorption method has emerged as one of the most promising techniques for pre-concentration of REEs, owing to the facile operation, organic solvent-free, and high adsorption efficiency. Recently, many kinds of materials have been proposed to be used for the removal of REEs from aqueous solutions, such as covalent organic frameworks, modified silica gels, super-cross-linked polymers, and some other porous nanoparticles. Compared to these popular materials, the ion-imprinted polymers (IIPs) exhibit excellent advantages in terms of environmental friendliness, toxicity, and production costs. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, the adsorption method has emerged as one of the most promising techniques for pre-concentration of REEs, owing to the facile operation, organic solvent-free, and high adsorption efficiency. Recently, many kinds of materials have been proposed to be used for the removal of REEs from aqueous solutions, such as covalent organic frameworks, modified silica gels, super-cross-linked polymers, and some other porous nanoparticles. Compared to these popular materials, the ion-imprinted polymers (IIPs) exhibit excellent advantages in terms of environmental friendliness, toxicity, and production costs. …”
Section: Introductionmentioning
confidence: 99%
“…pSWE can be used in HBV, HCV, hepatic toxicity, alcoholic liver disease, and autoimmune hepatitis related liver fibrosis[3739]. It can also be used as a screening tool for fibrosis detection at early stages[40], although evidence of benefit in this setting is limited.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Owing to their topological structural tunability, high specific area, facile preparation, and designable functionality, MOFs have gained extensive attraction in the field of adsorption. Compared with the other emerging adsorbents, such as covalent organic frameworks, hypercrosslinked polymers, and nanosilica composites, MOFs exhibit excellent advantages in terms of environmental friendliness, toxicity, and production costs. To date, various well-defined MOFs have been synthesized and utilized in adsorption of REEs. For example, an investigation reported that a Cu-based MOF (HKUST-1) exhibited a remarkable adsorption capacity of 353 mg/g for Ce­(III) because of its innate porosity and large specific surface area .…”
Section: Introductionmentioning
confidence: 99%